Meso-structure based phase field modeling for tensile behavior of UHPC materials - Wang, Tao; Li, Po; Tong, Teng; Li, Xiaobo; Liu, Zhao (Structures (Oxford), 2025)
Pre-peak multiple fine cracks and post-peak strain-hardening are features rendering ultra-high performance concrete (UHPC) different from conventional normal-strength concrete, which exhibits superior ductility. To promote its engineering applications, an accurate numerical tool is necessary to describe the crack initiation, nucleation, localization and propagation. Aiming at tensile behavior of UHPC materials, the numerical framework is proposed, which integrates statistical meso-scale mechanical damage model and elasto-plastic phase field model. Given properties of UHPC matrix, steel fibers, and interface, the meso-scale damage model gives the stress-strain relationship subject to monotonic tension, considering cracking bridging effect and matrix spalling. The predicted stress-strain relationship is subsequently converted into the elasto-plastic phase field model to study the failure mechanisms of UHPC materials at structural (macro-scale) level. A novel concept of thresholds of elastic and plastic strain energies is proposed to take the multi-cracking and crack localization of UHPC materials into account. The model is numerically realized through implicit, staggered time-integration algorithm. Its robustness is validated by several experimental paradigms, i.e., direct tension of dog-bone UHPC specimens, three-point bending of notched UHPC specimens, and flexural behavior of reinforced UHPC specimens. The related code in this study is released at GitHub repository for better analysis and design of various UHPC members. •Tensile stress-strain curve is related to the meso-structure of UHPC materials.•Meso-structure based crack bridging mechanism is integrated with the damage-plastic phase field model.•The model is implemented with Abaqus/Standard solver and is verified by several experimental paradigms.